Bioprospecção de atividades anti-incrustante e antifúngica dos estratos das macroalgas Asparagopseis Taxiformis (Rhodophyta, Bonnemaisoniaceae) - Oliveira, Jade del Nero (2022)
Marine macroalgae are one of the most important targets in the scope of bioprospecting for substances of interest from the sea due to the variety of metabolites produced and bioactivities related to these metabolites. The objective of the present work was to evaluate the antifouling and antifungal action of hexane (Hex), dichloromethane (DCM) and methanolic (MeOH) extracts from different collection points of the macroalgae Asparagopsis taxiformis. The antifouling bioassay was performed with juveniles of the bivalve mollusc Perna perna while the filamentous fungus Cladosporium cladosporioides was used for antifungal screening. The extracts were obtained by successive extraction methodology with solvents of three different polarities in order to expand the range of molecules obtained in the extraction process. The concentrations of extracts and incorporation in filter paper to perform the antifouling assay were prepared by calculating the natural concentration and the negative controls with filters soaked in the extraction solvent only. The antifouling action was evaluated by measuring the number of byssus produced by the molluscs and antifungal screening was analyzed by the halo of inhibition of growth and development of spores of the fungus. Antifouling activity was compared by ANOVA followed by Dunnett's test, while antifungal action was by visual inspection of the inhibition halo. The location of collection (or population of origin) and the polarity of the extract influenced the antifouling and antifungal activities. The population from Ilha Comprida was the only one that significantly inhibited fouling. The Hex extract stimulated the production of byssi while the MeOH fraction inhibited its production. The antifungal screening test revealed the stimulation of fungal production by the Hex fractions of all populations and the inhibition of fungal spores growth by the DCM and MeOH fractions, with the strongest antifungal effect being that of the extract in MeOH.